PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. BPR KITA DI BADUNG, PROVINSI BALI - Ni Made Amrita Anuttami; Ni Luh Putu Indiani (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to analyze the influence of leadership, organizational culture, and work motivation on employee performance at PT. BPR Kita in Badung, Bali. The data collection method is survey method using questionnaires. The analysis technique used is multiple linear regression. The results showed that leadership, organizational culture, and work motivation had a positive and significant influence on employee performance.